Influence of Convenience, Usability, Price, and Promotion on Reuse Intentions: Muslim Awareness Moderation - Febrina Adita Putri; Asyari (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2024)
Online transportation has transformed the transport industry by offering practical and innovative solutions embraced by the public. This study evaluates the impact of ease of use, usefulness, price, and online promotion on the intention to reuse online transportation services, with Muslim consumer awareness as a moderating variable. Focusing on Grab users in Jakarta, the research uses a quantitative approach with 110 respondents from South and Central Jakarta, analyzed using Warp PLS. The results show that ease of use, usefulness, and online promotion positively and significantly affect reuse intention, while price has a negative and significant impact. Muslim consumer awareness moderates the effects of ease of use, usefulness, and online promotion on reuse intention but does not moderate the effect of price. These insights aid online transportation service providers in crafting effective marketing strategies for Muslim consumers in Jakarta.